2022
DOI: 10.1109/tii.2021.3095466
|View full text |Cite
|
Sign up to set email alerts
|

iFaaSBus: A Security- and Privacy-Based Lightweight Framework for Serverless Computing Using IoT and Machine Learning

Abstract: As data of COVID-19 patients is increasing, the new framework is required to secure the data collected from various Internet of Things (IoT) devices and predict the trend of disease to reduce its spreading. This article proposes security and privacy-based lightweight framework called iFaaSBus, which uses the concept of IoT, Machine Learning (ML), and Function as a Service (FaaS) or serverless computing to diagnose the COVID-19 disease and manages resources automatically to enable dynamic scalability. iFaaSBus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In future work, we will expand the system so that joining a cloud federation platform is integrated with joining the blockchain network as well as incorporating resource requirements and availability in the HyperLedger model structure. Further, BlockchainBus framework can be integrated with iFaasBus 41 to improve the scalability in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In future work, we will expand the system so that joining a cloud federation platform is integrated with joining the blockchain network as well as incorporating resource requirements and availability in the HyperLedger model structure. Further, BlockchainBus framework can be integrated with iFaasBus 41 to improve the scalability in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the authors proposed a blockchain-based system to track COVID-19 infected patients globally [18]. Accordingly, while protecting the data security and privacy of the patients, it aimed to keep the spread of the disease under control by following the patients.Golec et al [6] suggested a Covid-19 detection study using IoT and ML in the framework called iFaasBus. In the study, they used a serverless platform for the processing power and storage required for the IoT.…”
Section: Related Workmentioning
confidence: 99%
“…With the accuracy rate in Machine Learning (ML) techniques reaching satisfactory levels, health studies using IoT and ML started to increase [5]. The data received from users through sensors are trained with ML models, and patients are directed to the nearest health institutions in case of a possible pandemic detection [6].…”
Section: Introductionmentioning
confidence: 99%
“…A serverless design, on the other hand, addresses most of the issues that developers experience. Using a serverless architecture, the machine learning models are properly handled and the resources are effectively managed [135]. As a result of this design, developers may spend more time and resources working on AI model training rather than server infrastructure management.…”
Section: Serverless Computingmentioning
confidence: 99%